2020
DOI: 10.3390/mi11100908
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Numerical Simulation of Particle Focusing and Separation in Viscoelastic Fluids

Abstract: Particle focusing and separation using viscoelastic microfluidic technology have attracted lots of attention in many applications. In this paper, a three-dimensional lattice Boltzmann method (LBM) coupled with the immersed boundary method (IBM) is employed to study the focusing and separation of particles in viscoelastic fluid. In this method, the viscoelastic fluid is simulated by the LBM with two sets of distribution functions and the fluid–particle interaction is calculated by the IBM. The performance of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…2019), channel flows (Coclite et al. 2020), stratified flows (Jyothi, Renganathan & Pushpavanam 2019) and viscoelastic flows (Ni & Jiang 2020). Hur et al.…”
Section: Introductionmentioning
confidence: 99%
“…2019), channel flows (Coclite et al. 2020), stratified flows (Jyothi, Renganathan & Pushpavanam 2019) and viscoelastic flows (Ni & Jiang 2020). Hur et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids can be considered as uniformly mixed and continuously flowing fluids based on the assumption. The physical properties of the nanofluid are determined by the properties of the base liquid and the nanoparticle 29,30 . Table 8 shows the physical property parameters of three metal nanoparticles and deionized water 31 at 25°C.…”
Section: Resultsmentioning
confidence: 99%
“…The physical properties of the nanofluid are determined by the properties of the base liquid and the nanoparticle. 29,30 Table 8 shows the physical property parameters of three metal nanoparticles and deionized water 31 at 25°C. The volume fractions of different water-based nanofluids namely Cu-water, Al-water and Ag-water were set to 2%.…”
Section: Nanofluidsmentioning
confidence: 99%
“…Another method of manipulating the equilibrium position of particles is through the use of viscoelastic liquids. Ni and Jiang [149] demonstrated that the equilibrium position can be controlled through the elasticity number, the ratio between inertial and elastic forces, with increasing elastic number resulting in positions closer to the channel wall.…”
Section: Fundamental Migration Dynamics Prohm and Starkmentioning
confidence: 99%